O sensoriamento remoto como ferramenta didática na educação profissional e tecnologica - Limana, Cristina Cippolat (2014)
This study addresses the integration and use of technology in professional and technological education level, with emphasis on remote sensing tools. The overall objective of the research was to conduct a diagnosis of the use of Remote Sensing technology, technical education, with technical courses in Agriculture, Information Technology, Sales, Agribusiness and Administration courses offered by these Instituto Federal Farroupilha Campus Jaguari RS. Methodologically the study started with literature search to identify work already developed on Remote Sensing in Vocational and Technical Education; after the field research and the audience were chosen, we applied a questionnaire consisting of two parts, the first part in order to identify and the second theoretical part, with questions specific knowledge about Remote Sensing. The next step was to organize the data collected, confection tables and graphs. From these data, we proceeded to an argumentative analysis. Some of the results showed that most students is the Course Technical Administration, women and residing in the municipality of Jaguari, approximately half of the sample said to have never heard of Remote Sensing, but claim to have interest in this subject and believe that the Remote Sensing may be linked in some way with your technical course, thus highlighting the importance of working together students and teachers, aimed at working concepts and theories about the Remote Sensing and that makes sense to the reality of each course.